Parkinsonian Symptomatology May Correlate with CT Findings before and after Shunting in Idiopathic Normal Pressure Hydrocephalus - Mitsuaki Ishii; Toshio Kawamata; Ichiro Akiguchi; Hideo Yagi; Yuko Watanabe; Toshiyuki Watanabe; Hideaki Mashimo (Parkinson's Disease)
We aimed to investigate the characteristics of Parkinsonian features assessed by the unified Parkinson's disease rating scale (UPDRS) and determine their correlations with the computed tomography (CT) findings in patients with idiopathic normal pressure hydrocephalus (iNPH). The total score and the scores for arising from chair, gait, postural stability, and body hypokinesia in the motor examination section of UPDRS were significantly improved after shunt operations. Stepwise multiple regression analysis revealed that postural stability was the determinant of the gait domain score of the iNPH grading scale. The canonical correlation analysis between the CT findings and the shunt-responsive Parkinsonian features indicated that Evans index rather than midbrain diameters had a large influence on the postural stability. Thus, the pathophysiology of postural instability as a cardinal feature of gait disturbance may be associated with impaired frontal projections close to the frontal horns of the lateral ventricles in the iNPH patients.